Darwin's sacred cause race, slavery and the quest for human origins - Desmond, Adrian J. 1947-; Moore, James R. 1947- (The University of Chicago Press, 2011)
There is a mystery surrounding Darwin: How did this quiet, respectable gentleman, a pillar of his parish, come to embrace one of the most radical ideas in the history of human thought? Darwin risked a great deal in publishing his theory of evolution, so something very powerful--a moral fire--must have propelled him. That moral fire, argue authors Desmond and Moore, was a passionate hatred of slavery. They draw on a wealth of fresh manuscripts, correspondence, notebooks, diaries, and even ships' logs to show how Darwin's abolitionism had deep roots in his mother's family and was reinforced by his voyage on the Beagle as well as by events in America. Leading apologists for slavery in Darwin's time argued that blacks and whites were separate species, with whites created superior. Darwin believed that the races belonged to the same human family, and slavery was therefore a sin.--From publisher description.
Keywords: Darwin, Charles / 1809-1882; Darwin, Charles <1809-1882>; Darwin, Charles -- 1809-1882; Evolution (Biology); Natural selection; Antislavery movements; Monogenism and polygenism; Evolutionstheorie; Abolitionismus